Freshwater lampreys and fishes of Turkey; a revised and updated annotated checklist 2020 - Çiçek, Erdogan; Sungur, Sevil; Fricke, Ronald (Zootaxa, 2020)
The current status of the inland waters ichthyofauna of Turkey is revised, and an updated checklist of the freshwater fishes is presented. The latest checklist included all species listed in the available previous study that was published in 2015, which is now updated after a period of five years. We revised the validity of previously accepted species and added newly described and reported species in Turkey. Some previously erroneously reported species and not established alien fishes were excluded from this checklist. A total of 384 fish species belonging to 20 orders and 34 families have been reported in the inland waters of Turkey. Among these, 15 species (3.9%) are non-native and 208 species (54.2%) are considered as endemic to Turkey. A total of 119 species previously reported from Turkey have been excluded from Turkish ichthyofauna list, either in the present study or in previous studies.